USING READER RESPONSE AND FIGURATIVE LANGUAGE TO ANALYZE WILLIAM HENLEY’S POEM ‘INVICTUS’ - Firmansyah, Rafi Umar; Widyaningrum, Agnes (Universitas 17 Agustus 1945 Semarang, 2024)
This research focuses on examining the types of figurative language used in selected poem by William Henley through reader response in order to get understanding to the overall meaning and the purpose behind the poem. Qualitative descriptive method applied in this research and the data will present in descriptive ways. Perrine’s theory is applied as a theoretical framework to analyze the figurative language. Meanwhile, Rosenblatt’s theory about reader response is used to analyze the data. The data of this research are from two sources, namely primary and secondary data. Primary data are taken from William Henley’s poem entitled ‘Invictus’. Secondary data are taken from other related literature such as journals, articles, book, and others supporting data. The result of analysis shows that the poem contained five distinct types of figurative language, such as: metaphor, symbolism, hyperbole, personification, and simile. In terms of reader response, the researcher found that both aesthetic and efferent approaches were demonstrated by the readers. These findings show how this analytical framework can be effectively applied to enhance the understanding of literary works.Keywords: figurative language, reader response, literature, poem, Invictus